Quantum dot-based material and preparation method thereof
By dispersing a specific proportion of polymer-modified carbon quantum dots and ABCD-type quantum dots in PMMA, the problem of insufficient dispersion and stability of quantum dots is solved, and high-stability and uniformly dispersed material preparation is achieved, which is suitable for a variety of applications. application.
Patent Information
- Application Number
- CN202411442740.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-10-16
AI Technical Summary
In the prior art, the dispersion and stability of quantum dots are the main issues that limit their application.
A specific ratio of polymer-modified carbon quantum dots and ABCD-type quantum dots are dispersed in PMMA, and high-speed stirring and ultrasonic dispersion technology are used to ensure uniform dispersion of the quantum dots.
The stability and distribution uniformity of quantum dots are improved, and materials with good temperature and humidity resistance and long service life are prepared, which are suitable for applications such as electrodes and heavy metal detection.
Abstract
Description
Technical Field
[0001] The present invention relates to the field of quantum dot materials, and in particular to a quantum dot-based material and a preparation method thereof. Background Art
[0002] Quantum dots are a kind of "quasi-zero-dimensional" nanomaterials with three-dimensional sizes in the nanometer order. Due to the quantum size effect, its electrons and holes are affected by quantum confinement in three dimensions, which makes the continuous energy band in the bulk material become a discrete discrete energy level structure. Semiconductor quantum dots have extremely broad application prospects in single electron devices, storage and various optoelectronic devices, such as spectral conversion and photoelectric conversion.
[0003] However, in the prior art, the dispersibility and stability of quantum dots are the main problems that limit their application. Summary of the invention
[0004] In order to solve the above problems, the first aspect of the present invention provides a quantum dot-based material, the preparation raw materials include: PMMA, polymer-modified carbon quantum dots, ABCD-type quantum dots;
[0005] Among them, element A is at least one of Na, Fe, Cd, and Zn; element B is at least one of Fe, Cd, Ga, Mg, Pb, Cs, and Cu; element C is In; element D is at least one of S, Br, and I, and the four elements A, B, C, and D are different.
[0006] Preferably, element A is Zn; element B is Cu; element C is In; and element D is S.
[0007] In one embodiment: the weight ratio of polymer modified carbon quantum dots to ABCD type quantum dots is 1:1.5-3.
[0008] Preferably, the weight ratio of polymer-modified carbon quantum dots to ABCD-type quantum dots is 1:2.
[0009] In one embodiment, a method for preparing polymer-modified carbon quantum dots comprises the following steps: adding an amine substance and methyl methacrylate to a non-polar solvent, reacting at 250°C for 15-20 hours, cooling to below 80°C, adding methyl methacrylate and benzoyl peroxide, stirring evenly, maintaining the temperature at 50-60°C and continuing the reaction for 24-36 hours, washing and purifying, and then drying to obtain polymer-modified carbon quantum dots.
[0010] In one embodiment, a method for preparing polymer-modified carbon quantum dots comprises the following steps: adding 1-methylundecylamine, N-dodecyl-2-acrylamide and methyl methacrylate to a non-polar solvent, reacting at 250°C for 15-20 hours, cooling to below 80°C, adding methyl methacrylate and benzoyl peroxide, stirring evenly, maintaining the temperature at 50-60°C and continuing the reaction for 24-36 hours, washing and purifying, and then drying to obtain polymer-modified carbon quantum dots.
[0011] Preferably, the preparation method of polymer-modified carbon quantum dots comprises the following steps: adding 1 mol of 1-methylundecylamine, 0.5-2 mol of N-dodecyl-2-acrylamide and 3-6 mol of methyl methacrylate to a non-polar solvent, reacting at 250°C for 15-20 hours, cooling to below 80°C, adding 5-10 mol of methyl methacrylate and benzoyl peroxide (benzoyl peroxide is 1-3% of the total mass of methyl methacrylate), stirring evenly, maintaining the temperature at 50-60°C and continuing the reaction for 24-36 hours, washing and purifying, and then drying to obtain polymer-modified carbon quantum dots.
[0012] Preferably, the ABCD type quantum dots are ZnCuInS / ZnS quantum dots; the diameter of the ZnCuInS / ZnS quantum dots is 1-10 nm.
[0013] Preferably, the diameter of the ZnCuInS / ZnS quantum dots is 4-5 nm. There is no particular restriction on the manufacturer of the ZnCuInS / ZnS quantum dots. The ZnCuInS / ZnS quantum dots in the present disclosure were purchased from Xi'an Qiyue Biology.
[0014] The preparation method of the material comprises the following steps:
[0015] S1: Add PMMA into chloroform and stir evenly;
[0016] S2: Add the polymer-modified carbon quantum dots to the solution obtained in step S1 and stir evenly;
[0017] S3: Add ABCD quantum dots to the solution obtained in step S2 and stir evenly;
[0018] S4: The solution obtained in step S3 is dispersed by ultrasonication, and then placed in a vacuum drying oven for drying at room temperature.
[0019] The material of the invention is prepared by mixing quantum dot powder with PMMA in a specific ratio, and adopting high-speed stirring and ultrasonic dispersion technology to ensure uniform dispersion of the quantum dots.
[0020] The quantum dot-based material can be used to prepare a ratio fluorescence sensor for detecting heavy metal ions in water, such as mercury, cadmium, lead, etc., and is particularly suitable for detecting mercury ions.
[0021] The preparation method of the ratio fluorescence sensor is a commonly used preparation method in the art and is not particularly limited.
[0022] Preferably, the preparation method of the ratiometric fluorescence sensor in the present application comprises the following steps:
[0023] Step 1: Pre-prepare quantum dot-based materials;
[0024] Step 2: 1.0 g of the material prepared in step 1 is ultrasonically dispersed in toluene, and then refluxed with 0.2 g of 3-(aminopropyl)dimethylethoxysilane for 0.5-3 hours to obtain modified particles; the modified particles are dispersed in dichloromethane, 80 mg of 5-(4-aminophenyl)-10,15,20-triphenylporphyrin is added, and refluxed for 2-5 hours to obtain an intermediate product;
[0025] Step 3: The intermediate product obtained in step 2 is dispersed in ethanol at a concentration of 0.5 wt %, and then a crystal film with a thickness of 1 μm is obtained on a polydimethylsiloxane substrate by spin coating to obtain a fluorescence ratio sensor.
[0026] Beneficial effects:
[0027] The present invention adopts polymer-modified carbon quantum dots, which can improve the stability and uniform distribution of carbon quantum dots; the prepared polymer-modified carbon quantum dots and ABCD-type quantum dots of a specific diameter are dispersed in PMMA to further prepare a material with high stability, good temperature and humidity resistance, and long service life.
[0028] The carbon quantum dot-based material prepared in the present invention has better stability and can be well used for electrodes, heavy metal detection, etc. DETAILED DESCRIPTION
[0029] The present invention is specifically described below by way of examples.
[0030] If not stated otherwise, all starting materials used were commercially available.
[0031] Example
[0032] Example 1
[0033] Example 1 provides a quantum dot-based material, and the preparation raw materials include: PMMA, polymer-modified carbon quantum dots, and ZnCuInS / ZnS quantum dots; the diameter of the ZnCuInS / ZnS quantum dots is 4-5nm, and they are purchased from Xi'an Qiyue Biology.
[0034] The preparation method of polymer modified carbon quantum dots comprises the following steps: adding 1 mol of 1-methylundecylamine, 1 mol of N-dodecyl-2-acrylamide and 4 mol of methyl methacrylate to toluene, reacting at 250°C for 16 hours, cooling to below 80°C, adding 6 mol of methyl methacrylate and benzoyl peroxide (benzoyl peroxide is 1% of the total mass of methyl methacrylate), stirring evenly, maintaining the temperature at 50-60°C and continuing the reaction for 30 hours, washing and purifying, and then drying to obtain polymer modified carbon quantum dots.
[0035] The preparation method of the material comprises the following steps:
[0036] S1: Add 10 g PMMA into 300 mL chloroform and stir evenly;
[0037] S2: Add 1 g of polymer-modified carbon quantum dots to the solution obtained in step S1 and stir evenly;
[0038] S3: Add ABCD quantum dots to the solution obtained in step S2 and stir evenly;
[0039] S4: After ultrasonically dispersing the solution obtained in step S3 for 8 hours, the solution is placed in a vacuum drying oven and dried at room temperature.
[0040] The weight ratio of polymer-modified carbon quantum dots to ABCD-type quantum dots is 1:2.
[0041] Example 2
[0042] Example 2 provides a quantum dot-based material, and the raw materials for preparation include: PMMA, polymer-modified carbon quantum dots, and ZnCuInS / ZnS quantum dots; the diameter of the ZnCuInS / ZnS quantum dots is 4-5nm, and they are purchased from Xi'an Qiyue Biology.
[0043] The preparation method of polymer modified carbon quantum dots comprises the following steps: adding 1 mol of 1-methylundecylamine, 0.5 mol of N-dodecyl-2-acrylamide and 5 mol of methyl methacrylate to toluene, reacting at 250°C for 16 hours, cooling to below 80°C, adding 6 mol of methyl methacrylate and benzoyl peroxide (benzoyl peroxide is 1% of the total mass of methyl methacrylate), stirring evenly, maintaining the temperature at 50-60°C and continuing the reaction for 30 hours, washing and purifying, and then drying to obtain polymer modified carbon quantum dots.
[0044] The preparation method of the material comprises the following steps:
[0045] S1: Add 10 g PMMA into 300 mL chloroform and stir evenly;
[0046] S2: Add 1 g of polymer-modified carbon quantum dots to the solution obtained in step S1 and stir evenly;
[0047] S3: Add ABCD quantum dots to the solution obtained in step S2 and stir evenly;
[0048] S4: After ultrasonically dispersing the solution obtained in step S3 for 8 hours, the solution is placed in a vacuum drying oven and dried at room temperature.
[0049] The weight ratio of polymer-modified carbon quantum dots to ABCD-type quantum dots is 1:1.5.
[0050] Example 3
[0051] Example 3 provides a quantum dot-based material, and the raw materials for preparation include: PMMA, polymer-modified carbon quantum dots, and ZnCuInS / ZnS quantum dots; the diameter of the ZnCuInS / ZnS quantum dots is 4-5nm, and they are purchased from Xi'an Qiyue Biology.
[0052] The preparation method of polymer modified carbon quantum dots comprises the following steps: adding 1 mol of 1-methylundecylamine, 2 mol of N-dodecyl-2-acrylamide and 6 mol of methyl methacrylate to toluene, reacting at 250°C for 16 hours, cooling to below 80°C, adding 6 mol of methyl methacrylate and benzoyl peroxide (benzoyl peroxide is 1% of the total mass of methyl methacrylate), stirring evenly, maintaining the temperature at 50-60°C and continuing the reaction for 30 hours, washing and purifying, and then drying to obtain polymer modified carbon quantum dots.
[0053] The preparation method of the material comprises the following steps:
[0054] S1: Add 10 g PMMA into 300 mL chloroform and stir evenly;
[0055] S2: Add 1 g of polymer-modified carbon quantum dots to the solution obtained in step S1 and stir evenly;
[0056] S3: Add ABCD quantum dots to the solution obtained in step S2 and stir evenly;
[0057] S4: After ultrasonically dispersing the solution obtained in step S3 for 8 hours, the solution is placed in a vacuum drying oven and dried at room temperature.
[0058] The weight ratio of polymer-modified carbon quantum dots to ABCD-type quantum dots is 1:3.
[0059] Comparative Example 1
[0060] A quantum dot-based material, the specific implementation method is the same as that of Example 1, except that: a method for preparing polymer-modified carbon quantum dots comprises the following steps: adding 2 mol of 1-methylundecylamine and 4 mol of methyl methacrylate to toluene, reacting at 250°C for 16 hours, cooling to below 80°C, adding 6 mol of methyl methacrylate and benzoyl peroxide (benzoyl peroxide is 1% of the total mass of methyl methacrylate), stirring evenly, maintaining the temperature at 50-60°C and continuing the reaction for 30 hours, washing and purifying, and then drying to obtain polymer-modified carbon quantum dots.
[0061] Comparative Example 2
[0062] A quantum dot-based material, the specific implementation method is the same as that of Example 1, except that: a method for preparing polymer-modified carbon quantum dots comprises the following steps: adding 2 mol of N-dodecyl-2-acrylamide and 4 mol of methyl methacrylate to toluene, reacting at 250°C for 16 hours, cooling to below 80°C, adding 6 mol of methyl methacrylate and 0.5 mol of benzoyl peroxide, stirring evenly, maintaining the temperature at 50-60°C and continuing the reaction for 30 hours, washing and purifying, and then drying to obtain polymer-modified carbon quantum dots.
[0063] Comparative Example 3
[0064] A quantum dot-based material, the specific implementation method is the same as that of Example 1, except that: a method for preparing polymer-modified carbon quantum dots comprises the following steps: adding 1 mol of 1-methylundecylamine, 1 mol of N-(N-octadecyl)acrylamide and 4 mol of methyl methacrylate to toluene, reacting at 250°C for 16 hours, cooling to below 80°C, adding 6 mol of methyl methacrylate and benzoyl peroxide (benzoyl peroxide is 1% of the total mass of methyl methacrylate), stirring evenly, maintaining the temperature at 50-60°C and continuing the reaction for 30 hours, washing and purifying, and then drying to obtain polymer-modified carbon quantum dots.
[0065] Performance Testing
[0066] (1) The quantum dot-based material prepared in the present application was placed at 85% humidity and 85°C for 48 hours and then the emission spectrum was tested. It was found that the half-width of the transparent materials of Examples 1-3 did not increase, but the half-width of Comparative Example 1, Comparative Example 2, and Comparative Example 3 increased by 17%, 21%, and 34%, respectively, indicating that the quantum dot material prepared by this method has high stability.
[0067] (2) The quantum dot-based materials prepared in different embodiments and comparative examples were prepared into ratiometric fluorescence sensors according to the following steps:
[0068] Step 1: Prepare quantum dot-based materials according to Examples 1-3 and Comparative Examples 1-3 respectively;
[0069] Step 2: 1.0 g of the material prepared in step 1 was ultrasonically dispersed in toluene, and then refluxed with 0.2 g of 3-(aminopropyl)dimethylethoxysilane for 2 hours to obtain modified particles; the modified particles were dissolved in dichloromethane, 80 mg of 5-(4-aminophenyl)-10,15,20-triphenylporphyrin was added, and refluxed for 3 hours to obtain an intermediate product;
[0070] Step 3: The intermediate product obtained in step 2 is dispersed in ethanol at a concentration of 0.5 wt %, and then a crystal film with a thickness of 1 μm is obtained on a polydimethylsiloxane substrate by spin coating to obtain a fluorescence ratio sensor.
[0071] Mercury ions of different concentration gradients were prepared to test the detection limit of the sensor. It was found that the sensors prepared in Examples 1-3 of the present invention had a low detection limit for Hg 2+ The detection limit of the sensor prepared in Comparative Example 1 was 0.85-0.91 pM for Hg 2+ The detection limit of the sensor prepared in Comparative Example 2 is 10.2 pM for Hg 2+ The detection limit of the sensor prepared in Comparative Example 3 is 10.5 pM for Hg 2+ The detection limit was 10.67 pM.
[0072] Due to the coordination reaction between mercury and porphyrin, the fluorescence of porphyrin decreases, while the fluorescence of the quantum dot-based materials prepared in Examples 1-3 of the present application remains basically unchanged. As the ratio of the two peak intensities changes, the sensor system increases, and Hg can be sensitively detected. 2+ .
[0073] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A quantum dot-based material, characterized in that: The preparation raw materials include: PMMA, polymer-modified carbon quantum dots, ABCD-type quantum dots; Among them, element A is at least one of Na, Fe, Cd, and Zn; element B is at least one of Fe, Cd, Ga, Mg, Pb, Cs, and Cu; element C is In; element D is at least one of S, Br, and I, and the four elements A, B, C, and D are all different.
2. The material according to claim 1, characterized in that: The weight ratio of polymer modified carbon quantum dots to ABCD type quantum dots is 1:1.5-3.
3. The material according to claim 1, characterized in that: The weight ratio of polymer-modified carbon quantum dots to ABCD-type quantum dots is 1:
2.
4. The material according to claim 1, characterized in that: The preparation method of polymer modified carbon quantum dots comprises the following steps: adding amine substances and methyl methacrylate into a non-polar solvent, reacting at 250° C. for 15-20 hours, and then cooling to below 80° C.
5. The material according to claim 4, characterized in that: The method for preparing polymer-modified carbon quantum dots also includes the following steps: adding methyl methacrylate and benzoyl peroxide, stirring evenly, maintaining the temperature at 50-60° C. and continuing the reaction for 24-36 hours, washing and purifying, and then drying to obtain polymer-modified carbon quantum dots.
6. The material according to claim 1, characterized in that: In the ABCD type quantum dots, element A is Zn; element B is Cu; element C is In; and element D is S.
7. The material according to claim 6, characterized in that: The diameter of the ABCD quantum dots is 1-10 nm.
8. The material according to claim 7, characterized in that: The diameter of the ABCD type quantum dots is 2-8 nm.
9. The material according to any one of claims 6 to 8, characterized in that: The diameter of the ABCD quantum dots is 4-5 nm.
10. A method for preparing the material according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1: Add PMMA into chloroform and stir evenly; S2: Add polymer-modified carbon quantum dots to the solution obtained in step S1 and stir evenly; S3: Add ABCD quantum dots to the solution obtained in step S2 and stir evenly; S4: The solution obtained in step S3 is dispersed by ultrasonication, and then placed in a vacuum drying oven for drying at room temperature.
Citation Information
Patent Citations
High-stability polymer-coated quantum dot fluorescent powder material and preparation method thereof
CN106753328A
Oil-solubility carbon quantum dots (OCDs), PMMA-coated OOCDs, and preparation method and application thereof
CN106916587A
Quantum dot film and preparation method thereof
CN107238973A
KR20240095052A